Assistance in Financial Management in Tourism Village in Banyuwangi: A Literature Study - Nur'aini, Nur'aini; Nichilo, Stefano de (Malacca: Journal of Management and Business Development, 2025)
This study explores the role of financial management assistance in enhancing the sustainability and economic growth of tourism villages in Banyuwangi, Indonesia. Through a literature review of studies published between 2020 and 2024, this article identifies key strategies, challenges, and opportunities in financial management for community-based tourism. The findings highlight the importance of capacity building, digital tools, and collaborative partnerships in improving financial literacy and management practices among local stakeholders. This study contributes to the growing body of knowledge on sustainable tourism development and provides recommendations for policymakers and practitioners.